Cryoprecipitate administration after trauma. (August 2016) - Olaussen, Alexander; Fitzgerald, Mark C.; Tan, Gim A.; Mitra, Biswadev
Abstract : Objectives: Haemorrhage remains among the most preventable causes of trauma death. Massive transfusion protocols, as part of 'haemostatic resuscitation', have been implemented in most trauma centres. Relative to the attention to the ideal ratio of red blood cells to fresh frozen plasma and platelets, cryoprecipitate treatment has been infrequently discussed. We aimed to outline the use of cryoprecipitate during trauma resuscitation and analyse outcomes in patients who received cryoprecipitate after hypofibrinogenaemia detection. Methods: A retrospective review of registry data on all major trauma patients (Injury Severity Score>15) presenting to a level I trauma centre over a 4-year period (2008–2011) was conducted. We selected all patients who had received cryoprecipitate and then analysed patients who had received cryoprecipitate following the detection of hypofibrinogenaemia (<1.0 g/l). Mortality at hospital discharge among hypofibrinogenaemic patients who had received cryoprecipitate was compared with that among patients who had not received cryoprecipitate. Results: Of 3996 trauma patients, 3571 had fibrinogen levels recorded. Most patients ( n =3517, 98.5%) had initial fibrinogen counts of 1.0 g/l or higher, and cryoprecipitate was administered to a small proportion of these patients ( n =126, 3.6%). Of the 54 patients with hypofibrinogenaemia on arrival, one patient died immediately and was excluded from further analysis. Of the 53 patients, 30 received cryoprecipitate and 28/53 died (53%). There was no difference in mortality between those who had received and those who had not received cryoprecipitate (14/30 vs. 14/23, P =0.31). Conclusion: Administration of cryoprecipitate was uncommon during trauma resuscitation, even among patients with hypofibrinogenaemia on presentation. This study provides no evidence towards improved outcomes from administration of cryoprecipitate.